Validity, Practicality, and Effectiveness of Ludo Cartesius Learning Media to Improve Understanding of Mathematical Concepts - Sumadi, Iman Putra; Kusmayadi, Tri Atmojo; Fitriana, Laila (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Abstract mathematics learning requires media in outlining the material so that it can be well received by students. Media can help students understand and recall explanations from the teacher and test students' understanding more deeply. This research was conducted with the aim of knowing the validity of Ludo Cartesius' learning media to improve understanding of mathematical concepts in class VIII students at junior high school. This research will apply development research design with ADDIE approach developed by Robert Maribe Brach. The ADDIE stages include analysis, design, development, implementation, and evaluation. The Population in this study were all eighth grade students at junior high school. The research sample was 27 students who were taken randomly using cluster random sampling technique. The instruments used include media expert assessment sheets, material expert assessments, student and teacher response questionnaires, as well as pretest and posttest understanding of mathematical concepts. The average value of media experts from the three validators of Dokar's media is 95.61. The average value of media experts from the three validators of Dokar's media is 92.36. The results showed that the Dokar media was categorized as "very valid" in terms of media experts and material experts and this media was suitable for use in class VIII students at junior high school. Dokar media is classified as practical media based on the average percentage of student and teacher responses, namely 86.23% and 85.83%. Dokar media is an effective medium based on the t-test (paired sample t-test) p value (0.000)<α (0.05) so that the posttest score is better than the pretest.